Multi-wavelength 2-micron cladding pumped thulium - Ytterbium co-doped fiber laser using broad band fiber reflector - Babar, Ibrahim M.; Yasin, Moh; Harun, Sulaiman Wadi; Jusoh, Zulzilawati; Das, Shyamal; Paul, Mukul Chandra (Old City Publishing, 2017)
A new multi-wavelength Thulium-Ytterbium co-doped fiber (TYDF) laser with an all fiber linear cavity operating at 2μm is presented. A broadband fiber reflector (BBFR) is employed along with Fresnel reflection from the output ferrule to oscillate light within the cavity to produce an intense laser. The multiple energy states in the ground state of Tm3+ ions due to stark splitting produces a broad spectrum which is converted into multi-wavelength spectra because of photo-darkening effect. The reason for photo-darkening is the existence of color centres within the Thulium- Ytterbium co-doped silica fiber.